Role of Satisfaction in Mediating the Effect of Services Quality on the Customers’ Loyalty in the Village Credit Institutions of Pekraman, Indonesia - Anak Agung Ngurah Gede Sadiartha; Gusti Ayu Mirah Apsari (Journal of Business and Social Review in Emerging Economies, 2018)
Loyalty is a deep commitment to repurchase a product or service that becomes a preference consistently in the future by repurchasing the same product. The problem formulation in this study is how are the direct and indirect effects of services quality through satisfaction on the consumers’ loyalty.  This study aims to know the direct and indirect effect of services quality through satisfaction on the consumers’ loyalty. The study was conducted by the village credit institution of Pekraman, Tabanan located in Gajah Mada street 107, Tabanan. The number of samples is 94 customers with slovin’s formula and accidental sampling method. The techniques of data collection used were interviews, documentation, literature review and questionnaire. The research instruments used were validity test and reliability test. The technique of data analysis used was path analysis with sobel test. Based on the result of calculation, it showed that the services quality had a positive and significant effect on the customers’ satisfaction in the village credit institution of Pekraman, Tabanan as many as  0,000 < 0,05. Thus, H0 was rejected and H1 was accepted. The customers’ satisfaction had a positive and significant effect on the customers’ loyalty in the village credit institution of Pekraman, Tabanan as many as 0,000 < 0,05. The services quality had a positive and significant effect of the customers’ loyalty in the village credit institution of Pekraman, Tabanan as many as 0,000 < 0,05. Thus, H0 was rejected and H3 was accepted. Based on the result of calculation, it showed that Zcount (5,323)> Z table (1,96). Thus, the customers’ loyalty can mediate the relationship between customers’ services quality and loyalty on the village credit institution of Pekraman, Tabanan. For the services quality, it is needed to improve the services given to the customers. For instance, it is provided the more exciting interest adjusted to the type of savings chosen by the customers so they will feel more satisfied and can develop their loyalty